Analisis Pengukuran Kinerja Operasional CV Fortis Sportswear Indonesia Menggunakan Pendekatan Balanced Scorecard (BSC) (Jurnal Manajemen Kreatif dan Inovasi, 2026)
This study examined the operational performance of CV Fortis Sportwear Indonesia (FSI) before implementing the Balanced Scorecard approach, identified the factors that hindered each Balanced Scorecard perspective, and analyzed the company's operational performance when measured using this approach.This study employed a descriptive quantitative method, aimed at providing a systematic, factual, and accurate overview of CV FSI's operational performance based on the Balanced Scorecard approach. Data were collected through interviews, questionnaires, observations, and literature review to obtain information related to the four main perspectives of the Balanced Scorecard: financial, customer, internal business processes, and learning and growth.After implementing the Balanced Scorecard, the performance evaluation of CV Fortis Sportswear Indonesia became more comprehensive compared to the previous system, which focused solely on financial aspects. The financial perspective showed improvement, but the customer aspect remained adequate, with declining retention and increasing complaints. Internal business processes still faced inefficiencies and quality issues, despite the introduction of new technology. The learning and growth perspective also improved through training, but employee satisfaction remained moderate. The Balanced Scorecard proved to provide a more comprehensive performance assessment and identified the need for improvements in customer, internal processes, and human resource development.